Scoliosis and spinal muscular atrophy in the new world of medical therapy: providing lumbar access for intrathecal treatment in patients previously treated or undergoing spinal instrumentation and fusion. Issue 4 (July 2019) - Labianca, Luca; Weinstein, Stuart L.
Abstract : This study describes a new procedure for a safer and easier access for the intrathecal injection of the recently approved nusinersen therapy in spinal muscular atrophy. This therapy changed the natural history of the disease, but, to date, scoliosis surgery was an excluding criteria for nusinersen therapy. The bone mass, due to the posterior spinal fusion of the scoliosis surgery, prevents the needle for the nusinersen administration from intervertebral access. This is a single-center, single-surgeon case series descriptive study. A laminotomy at the L3–L4 level was performed to provide safer access for the intrathecal injection. The procedure was carried out during the scoliosis surgery in patients who underwent posterior spinal fusion (PSF) after the nusinersen therapy was introduced, whereas for those who underwent PSF earlier, a second procedure was necessary to perform a laminotomy. A fat grafting was used to prevent bone overgrowth in the laminotomy. Markers were applied as radiographic references for the intrathecal injection. Five patients were enrolled, four females and one male. The mean age of the patients was 11 years. Three patients underwent PSF before the introduction of the nusinersen therapy. Two patients underwent PSF after the nusinersen therapy was available. All of them underwent a laminotomy with a fat grafting at the L3–L4 laminotomy level and received nusinersen therapy without complications. The procedure described is simple and effective in providing safe intrathecal access to make these patients eligible for such important therapy.